2016
DOI: 10.1007/s12010-016-2151-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Lipid Production of Chlorella Pyrenoidosa Cultivated in Municipal Wastewater by Magnetic Treatment

Abstract: Despite the significant breakthroughs in research on microalgae as a feedstock for biodiesel, its production cost is still much higher than that of fossil diesel. One possible solution to overcome this problem is to optimize algal growth and lipid production in wastewater. The present study examines the feasibility of using magnetic treatment for enhancement of algal lipid production and wastewater treatment in outdoor-cultivated Chlorella pyrenoidosa. Results confirmed that magnetic treatment significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Deamici et al [ 96 ] verified that 60 mT applied throughout the cultivation increased by 20.5% and 24.8% in terms of biomass and carbohydrate content, respectively. Han et al [ 100 ] observed that 0.5 T stimulated 12% biomass and 10% lipid productivity when MF was applied throughout the cultivation. Chu et al [ 95 ] verified the effects of MF and nitrate concentration on the growth of Nannochloropsis oculate .…”
Section: The Effects Of Mfs On Microalgaementioning
confidence: 99%
“…Deamici et al [ 96 ] verified that 60 mT applied throughout the cultivation increased by 20.5% and 24.8% in terms of biomass and carbohydrate content, respectively. Han et al [ 100 ] observed that 0.5 T stimulated 12% biomass and 10% lipid productivity when MF was applied throughout the cultivation. Chu et al [ 95 ] verified the effects of MF and nitrate concentration on the growth of Nannochloropsis oculate .…”
Section: The Effects Of Mfs On Microalgaementioning
confidence: 99%
“…At present, biodiesel's production cost is from 1.5 to 3-fold more than fossil diesel due to the high cost of raw feedstocks and unavailability of oil crops utilized for human food consumption [2]. Algal biomass are considered an attractive natural source of bioactive materials that can be utilized in several applications such as food industry [3], pharmaceuticals [4], cosmetics [5], biogas and biodiesel [6,7], antimicrobial and antioxidant activities [3,8], aquaculture [9][10][11][12], biofertilizers and bioremediation [13][14][15][16]. Therefore, the screening of native microalgae species is necessary to realize a potent algal database with effective commercial biotechnological applications [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Algal biomass is an attractive inbred bioactive substances that can be used in different industrial uses including aquaculture diet feed additive [ 10 ], aquaculture water-conditioner [ 11 ], plant growth biostimulants [ 12 ], the food industry [ 13 ], pharmaceuticals [ 14 ], antimicrobial substances [ 15 ], cosmetics [ 16 ], bioremediation [ 17 ], biodiesel [ 18 , 19 ], and crude bio-oil [ 20 ]. One of the most interesting applications is the production of biodiesel from microalgae due to the relatively high lipid productivity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%